Teaching resources in the social sciences for social studies teachers - Agno, Lydia Navarro 1932-
The study aimed to determine what teaching resources in the social studies curricular offerings and to the national development goals of the state could be utilized to enrich the knowledge of social studies teachers. It used content analysis of the social studies scope and sequence charts and the preparation of teaching resources for the teachers. The content analysis showed that new social studies draw their content materials from the different social science disciplines. There is also a high correlation between the social science coverage in the elementary and secondary level, which are also interdisciplinary. The concepts of environment, resources, interdependence, social organization, heritage, values, change, and economic development were considered for inclusion in the study as they are perceived to be most relevant to the development goals of the state.